Construindo cenários e estratégias de aprendizagem integradoras (inclusivas) - Alves, Maria Dolores Fortes (2013)
The current phenomenon in society of intolerance is the result of culture, and the paradigm of good/evil, beautiful/ugly, man/woman, normal/abnormal, right/wrong. It seems to be a consequence, the damage of some by others. The other, who may have a disability or physical difference, is seen as different in the eyes of this Cartesian paradigm, which is dualistic and fragmented. And yet, the fear of the new, of what is different, cause our narcissistic view of others to judge the other as inferior and often intimidating because of their physical appearance, culture, or social status. But we know that we are all made of the same material - carbon atoms. Nevertheless the human genetic code, and that of all species on the planet, have a unique characteristic. We are not replicable beings. Diversity is constant and, from the biologic point of view, favors the survival of the species. Thus, from the theoretical foundations of Ecosystemic Thinking, Complexity and Transdisciplinarity, the objective of this work is to present a guide for teachers and/or social agents (educators, psychologists, educational psychologists, social workers, business managers, etc.) so they can build "Integrative Learning Strategies" which promote inclusive processes. In the light of Transdisciplinary and Complex methodologies, an action research was conducted with students in two courses in order to develop Integrative Learning Strategies. Thus, based on the theories of Complexity, Interdisciplinarity, Transdisciplinarity and Ecosystemic Thinking, categories were developed, and based on these categories a qualitative analysis of accounts by students participating in the courses was conducted. The analysis showed that inclusion was above all an attitude of reverence for life, to legitimize him/herself and the other, recognize him/herself as unique, singular, multidimensional, multiple and complex. And the Integrative Learning Strategies, with its guiding principles (motivation, openness, ethics, self-organization, sensitive listening, subjectivity and inter subjectivity, ecologic action, third person inclusive, thought hologramatic, emerging, contextualized, dialogical thinking and self-consciousness) had a fundamental role in helping the subjects go beyond a fragmented reality, that is dualistic and dichotomist, helping the subjects develop new perceptions and attain new levels of reality. These levels contributed to the co-construction, to "human habitat" of cooperation and lovingness, since these are part of our human biology and socially legitimate every being, for the equilibrium of the Triangle of Life and for building a world for all of us